Education, skill training, and lifelong learning in the era of technological revolution - Jinyoung Kim; Cyn-Young Park (Asian Development Bank (ADB), 2020)
Rapid technological development makes skills depreciate faster than in the past while new technologies generate gaps in workers' skills and call for the acquisition of proper skills and lifelong learning. Proper skill mixes for future jobs include strong cognitive skills, basic information and communication technology, and analytical skills, as well as a range of noncognitive skills such as creativity, problem-solving, critical thinking, and communication. Retraining and reskilling workers is also crucial. All these changes lead to a major rethinking of education and skill training throughout a person's life. This paper reviews the recent studies on human capital and skill formation in the era of rapid technological progress. Findings from these studies particularly in labor economics can shed light on new directions for lifelong education policies.
Keywords: I25; I28; J00; J24; O15; O33; 330; education policy; lifelong learning; population aging; technology